Life-saving ECMO and fiberoptic bronchoscope thrombectomy for severe respiratory dysfunction in pregnancy: a case report - Liu, Chiwen; Jiang, Li; Yuan, Donglan; Xu, Xinlan; Wei, Jing (Frontiers in Medicine, 2025)
BackgroundSevere respiratory dysfunction during pregnancy, though rare, represents a life-threatening condition, often presenting as dyspnea and respiratory distress. Pregnant patients with pulmonary vascular disease are particularly vulnerable, facing a poor prognosis and a heightened risk of mortality. This report aimed to highlight strategies for mitigating severe complications in high-risk pregnant women and to provide valuable insights into effective clinical management approaches.Case presentationWe presented the case of a 40-year-old pregnant woman who required hospitalization for intensive monitoring of vital signs. On admission, her temperature was 36.2°C, respiratory rate 25 breaths per minute, blood pressure 108/84 mmHg, and heart rate 87 beats per minute. Notably, her resting blood oxygen saturation was critically low at 80%. A bedside chest X-ray revealed right lung atelectasis with increased interstitial markings and thickening in the left lung. Computed tomographic angiography (CTA) of the thoracic aorta demonstrated a mildly dilated and tortuous bronchial artery supplying the right lung. The patient subsequently developed pulmonary hemorrhage, atelectasis, and pulmonary infection, ultimately progressing to respiratory failure due to congenital bronchial artery malformation. A multidisciplinary intervention strategy was implemented, incorporating extracorporeal membrane oxygenation (ECMO), bronchial artery embolization, fiberoptic bronchoscopic suctioning, alveolar lavage, and comprehensive life support measures. ECMO combined with fiberoptic bronchoscope thrombectomy proved to be instrumental in stabilizing her condition, leading to significant clinical improvement and a successful discharge.ConclusionPulmonary vascular disease-induced hemodynamic instability imposed a substantial risk of circulatory shock in pregnancy. This case underscored the efficacy of ECMO and fiberoptic bronchoscope thrombectomy in the management of severe respiratory dysfunction during pregnancy, advocating for their integration into clinical practice for similar high-risk cases.